Investigating the use of titanium dioxide (TiO2) nanoparticles on the amount of protection against UV irradiation - Reza Ghamarpoor; Akram Fallah; Masoud Jamshidi (Scientific Reports, 2023)
Abstract In this study, three samples of commercial titanium dioxide nanoparticles (TiO2) in different sizes were used to investigate their effect on the formulation of sunscreen creams. The aim was to evaluate their role in the performance of sunscreens (i.e. SPF, UVAPF, and critical wavelength). Then the particle size of these samples was determined by photon correlation spectroscopy methods. As a result, the size of primary particles was reduced by using milling and homogenization methods at different times. The results showed that the particle size of samples TA, TB, and TC in the ultrasonic homogenizer decreased from 966.4, 2745.8, and 2471.6 nm to 142.6, 254.8, and 262.8 nm, respectively. These particles were used in the pristine formulation. Then the functional characteristics of each formulation were determined by standard methods. TA had the best dispersion in cream compared to other samples due to its smaller size (i.e. 142.6 nm). For each formulation, two important parameters, including pH and TiO2 dosage, were investigated in different states. The results showed that the formulations prepared with TA had the lowest viscosity compared to formulations containing TB and TC. SPSS 17 statistical software analysis of variance showed that the performance of SPF, UVAPF and λc in formulations containing TA had the highest levels. Also, the sample containing TAU with the lowest particle size values had the highest protection against UV rays (SPF). According to the photocatalytic functionality of TiO2, the photodegradation of methylene blue in the presence of each nanoparticle of TiO2 was studied. The results showed that smaller nanoparticles (i.e. TA) had more photocatalytic activity under UV–Vis irradiation during 4 h (TA (22%) > TB (16%) > TC (15%)). The results showed that titanium dioxide can be used as a suitable filter against all types of UVA and UVB rays.